Evaluation of Rural Environmental Governance Efficiency and Influencing Factors in the Yangtze River Delta Region under the Goal of “Dual Carbon” - Chen, Mengjiao; Pan, Yusang; Ma, Wenjia; Wang, Kai (International Journal of Global Economics and Management, 2024)
In the face of deteriorating ecological problems such as pollution from agricultural production, pollution from farmers' lives, and pollution from township industries in the Yangtze River Delta region, as well as the plight of an imperfect rural environmental governance system and insufficient governance capacity, there is an urgent need to set up a comprehensive assessment system for the efficiency of rural environmental governance, improve the rural environmental governance system, and modernize the capacity of environmental governance. This project will firstly sort out the research results of rural environmental governance at home and abroad, and systematically analyze the theory of rural environmental governance; secondly, analyze the spatial changes of environmental pollution in rural areas during different periods, and analyze the efficiency of environmental governance in the rural areas of the Yangtze River Delta in different dimensions; finally, analyze the influencing factors of the efficiency of rural environmental governance under the constraints of the target of “double carbon”, and analyze the factors of economic development, economic development, and the impacts on the efficiency of rural environmental governance. Finally, we analyze the influencing factors of rural environmental governance efficiency under the constraint of the “double carbon” goal, and analyze the impacts of economic development, policy formulation, villagers' motivation and other factors on rural environmental governance efficiency. The results of this study provide an important reference for further promoting the realization of the dual-carbon goal and scientific environmental governance in the Yangtze River Delta region, and also provide a strong case study and reference for environmental governance strategies in other regions.